Application of Low Code Development Platform in Digital Project Management - Wei, Wenting; Hou, Xiaoe (2024 International Conference on Internet of Things, Robotics and Distributed Computing (ICIRDC), 2024)
Digital transition has become an integral part of business progress as it relates to entering the digital project management system for enterprise information building. The adoption of the low-code development platform is an important option for the digital project management of the enterprise due to the ability of low-code development platform to excel in efficiency and flexibility compared to the conventional manual coding method. This study sets out to conduct a comparative experiment to design the grid digital project management system using the low-coded development platform and traditional manual coding method respectively. After system was developed, in terms of development cycle, system response time, RPS system throughput, the difference between the two systems was tested and compared and the results showed that the development of the low-code development platform was significantly better than the traditional manual coding method in system response time, system throughput system. In particular, the average system response time of the low-code group is 2.1 seconds, while the average system response time of the traditional coding group is 3.3 seconds; the average RPS of the low-code group is 1,283, while the average RPS of the traditional coding group is 902, suggesting that the low-code development platform can effectively improve the performance and interactivity of the digital project management system and bring benefits to the enterprise informationization.